Cellulose Ethers from Banana (Musa balbisiana Colla) Blossom Cellulose: Synthesis and Multivariate Optimization - Safira Zidna Salama; Maulidan Firdaus; Venty Suryanti (Indonesian Journal of Chemistry, 2024)
Cellulose ethers are biocompatible polymers which have attracted considerable attention for various applications due to their physical and mechanical properties. The present work aims to find the optimum condition for synthesizing cellulose ethers from banana blossom cellulose (BBC) such as methylcellulose (MC), carboxymethyl cellulose (CMC) and hydroxypropyl cellulose (HPC). The ultrasonication-assisted method as an energy source is used to shorten the synthesis time at room temperature and obtain high yields. The influences of various parameters (NaOH concentration, etherification agents, and sonication time) were analyzed using a multivariate statistical modeling response surface methodology (RSM). The materials were characterized by FTIR, SEM, and TGA. The cellulose ethers obtained have the potential as food additives with DS values of 2.0, 0.7, and 0.86, respectively. MC was synthesized optimally with a yield of 96.52% using a composition of cellulose (0.4 g), 50% (w/v) NaOH (10 mL) and dichloromethane (6 mL). CMC was synthesized optimally with a yield of 98.26% using a composition of cellulose (0.4 g), 30% (w/v) NaOH (2 mL) and monochloroacetic acid (1 g). HPC was synthesized optimally with a yield of 97.51% using a composition of cellulose (0.4 g), 10% (w/v) NaOH (2 mL) and propylene oxide (1.5 mL).